Natural Language Processing and Chinese Computing : 4th CCF Conference, NLPCC 2015, Nanchang, China, October 9-13, 2015, Proceedings - Li, Juanzi; Ji, Heng.; Zhao, Dongyan; Feng, Yansong; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 4th CCF Conference, NLPCC 2015, held in Nanchang, China, in October 2015. The 35 revised full papers presented together with 22 short papers were carefully reviewed and selected from 238 submissions. The papers are organized in topical sections on fundamentals on language computing; applications on language computing; NLP for search technology and ads; web mining; knowledge acquisition and information extraction.
Keywords: Natural language processing (Computer science).; Multimedia systems; Information storage and retrieva; Database management; Data mining; Natural Language Processing (NLP).; Information Systems Applications (incl. Internet).; Multimedia Information Systems; Information Storage and Retrieval; Database Management; Data Mining and Knowledge Discovery